1992
DOI: 10.1002/ana.410310412
|View full text |Cite
|
Sign up to set email alerts
|

Preferential loss of striato‐external pallidal projection neurons in presymptomatic Huntington's disease

Abstract: We have reported previously that striatal projection neurons are differentially affected in the course of Huntington's disease, and in a prior patient report we noted that differential loss of striatal projection neurons occurs also in patients with presymptomatic Huntington's disease. Striatal neurons projecting to the external segment of the globus pallidus or the substantia nigra show evident loss, whereas those projecting to the internal segment of the globus pallidus appear relatively spared at presymptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
194
2
2

Year Published

1993
1993
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 337 publications
(219 citation statements)
references
References 19 publications
21
194
2
2
Order By: Relevance
“…The projection neurons are themselves divided into two classes. Both types contain GABA as a primary neurotransmitter, but of the two populations of striatal projection neurons, those of the indirect pathway (i.e., enkephalin/GABA-containing neurons) are affected first, thus providing an anatomical substrate for the increased movement that is the hallmark of HD (Reiner et al, 1988;Albin et al, 1992). In later stages of adult HD, both populations of striatal projection neurons are affected, with concomitant loss of markers of the direct pathway (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The projection neurons are themselves divided into two classes. Both types contain GABA as a primary neurotransmitter, but of the two populations of striatal projection neurons, those of the indirect pathway (i.e., enkephalin/GABA-containing neurons) are affected first, thus providing an anatomical substrate for the increased movement that is the hallmark of HD (Reiner et al, 1988;Albin et al, 1992). In later stages of adult HD, both populations of striatal projection neurons are affected, with concomitant loss of markers of the direct pathway (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…AAV-GDNF improved rotorod performance, delayed and attenuated clasping behavior, and preserved the number and size of striatal neurons in this model. Both clinical (34)(35)(36) and preclinical (3,31,33) studies suggest that HD symptoms can occur before the frank loss of striatal neurons. The prevention of neuronal atrophy by AAV-GDNF suggests that an early aspect of the degenerative process that mediates symptom onset might be prevented by this treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Polyglutamine expansion leads to a conformational change in the huntingtin protein, causing the formation of large aggregations in the nucleus and cytoplasm. These htt and mutant htt (mhtt) genes are expressed ubiquitously in human tissues, spiny neurons of the putamen and caudate nucleus in HD (Arrasate et al 2004;Albin et al 1992). The recent evidence suggested that the involvement of ROS in HD pathogenesis is by dysfunctioning of the mitochondrial complex II (Calkins et al 2005).…”
Section: Huntington's Diseasementioning
confidence: 99%